Types of fears reported by immigrant Pontian Greeks from the former Soviet Union and by native Greeks - Papadopoulou, Eleni; J. Pickersgill, Mary (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF